2015
DOI: 10.1080/13825585.2015.1041449
|View full text |Cite
|
Sign up to set email alerts
|

Age- and education-adjusted normative data for the Montreal Cognitive Assessment (MoCA) in older adults age 70–99

Abstract: The original validation study for the Montreal Cognitive Assessment (MoCA) suggests a cutoff score of 26; however, this may be too stringent for older adults, particularly for those with less education. Given the rapidly increasing number of older adults and associated risk of dementia, this study aims to provide appropriate age- and education-adjusted norms for the MoCA. Data from 205 participants in an ongoing longevity study were used to derive normative data. Individuals were grouped based on age (70-79, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
122
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 16 publications
15
122
1
1
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
“…We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31]. Lower level of education was significantly associated with lower scores, correlating with results from other studies [11][12][13][14][15][16][17][18][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations